The Urgency of Developing E-Learning Moodle Substance Pressure Topic on Guided Inquiry Learning to Improve Mastery of Scientific Concepts and Communication - Widya Rahmatika Rizaldi*; Winny Liliawati; Achmad Samsudin (Universitas Syiah Kuala, 2023)
Constraints found in science learning in junior high schools lead to low mastery of scientific concepts and communication skills. Therefore, this study aims to describe the early stages of analysis related to urgency as the basis for product development in the form of e-learning moodle in guided inquiry learning to improve mastery of scientific concepts and communication skills on substance pressure material and its application to everyday life. The method used was descriptive research using literature studies, curriculum analysis, needs analysis questionnaires, open interviews with science teachers, and student ability surveys using question instruments. The research subjects comprised 81 students and two junior high school science teachers. Based on the analysis results, it is known that students want a new learning atmosphere that involves several learning media and practicum-based learning. But the reality of learning still uses traditional methods and a single learning resource, namely textbooks. The development of learning media in the form of moodle e-learning with the guided inquiry learning model is expected to assist teachers in facilitating a new, fun learning atmosphere and involving practicum activities to improve students' mastery of concepts and scientific communication skills